2015
DOI: 10.2298/abs150116060m
|View full text |Cite
|
Sign up to set email alerts
|

Palynomorphological study of Dianthus petraeus waldst. et kit. (Caryophyllaceae)

Abstract: The pollen morphology of Dianthus petraeus (Caryophyllaceae), which is endemic to the Balkans, has been examined by both light and scanning electron microscopy in order to provide taxonomically valuable characters that might be used in the classification of the Caryophyllaceae, as well as to contribute to the pollen atlas of Serbian apiflora. The pollen grains of D. petraeus are radially symmetrical, apolar, spheroidal and medium-sized. The mean of the pollen diameter is 45.5?1.4 ?m. The scul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Many researchers believed that the pores number in Caryophyllaceae is a stable characteristic (Dang, ; Doğan & Ömer Erdem, ; Faegri & Iversen, ; Mačukanović‐Jocić et al, ; Mostafavi & Mehregan, ; Wan et al, ; Yıldız, ). In this study, we found that the pore number of Pseudostellaria is stable, being 12–16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers believed that the pores number in Caryophyllaceae is a stable characteristic (Dang, ; Doğan & Ömer Erdem, ; Faegri & Iversen, ; Mačukanović‐Jocić et al, ; Mostafavi & Mehregan, ; Wan et al, ; Yıldız, ). In this study, we found that the pore number of Pseudostellaria is stable, being 12–16.…”
Section: Discussionmentioning
confidence: 99%
“…The pollen morphological characteristics provide an important basis for phylogenetic relationships and taxonomy of plants (Du, Zhao, & Liu, ; Gul et al, ; Liu, Zhao, Liu, Xi, & Zhang, ; Ullah et al, ; L. Wang, Gu, Zhao, & Liu, ). The pollen morphological features of Caryophyllaceae, for example, the pores number, microechini density, and surface ornamentation have been generally used in different classification levels, such as intergeneric, intrageneric, interspecific, and intraspecies levels (Aktaş, Altan, Ozdemir, Baran, & Garnatje, ; Ataşlar, Potoglu Erkara, & Tokur, ; Barkoudah, ; Chanda, ; Cui, Wang, Gu, & Liu, ; Erdtman, ; Iwarsson, ; Kızılpınar, Özüdoğru, Özmen, Erik, & Doğan, ; Mačukanović‐Jocić, Jarić, & Mladenović, ; McNeill & Basset, ; Nejad Falatoury, Assadi, & Ghahremaninejad, ; Nejad Falatoury, Ghahremaninejad, & Assadi, ; Parent & Richard, ; Perveen & Qaiser, ; Skvarla & Nowicke, ; Yıldız, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family Caryophyllaceae has subspheroidal pollen shape pantoporate, and species are differentiated by number of pores (Mačukanović‐Jocić, Jarić, & Mladenović, ; Ullah, Zafar, Ahmad, Dilbar, et al, ). This study also showed that the pollen morphology shape is subspheroidal, and pantoporate.…”
Section: Discussionmentioning
confidence: 99%